2009
DOI: 10.1021/jp806638e
|View full text |Cite
|
Sign up to set email alerts
|

SiO2 Atomic Layer Deposition Using Tris(dimethylamino)silane and Hydrogen Peroxide Studied by in Situ Transmission FTIR Spectroscopy

Abstract: The atomic layer deposition (ALD) of silicon dioxide (SiO 2 ) was initially explored using a variety of silicon precursors with H 2 O as the oxidant. The silicon precursors were (N,N-dimethylamino)trimethylsilane) (CH 3 ) 3 SiN(CH 3 ) 2 , vinyltrimethoxysilane CH 2 dCHSi(OCH 3 ) 3 , trivinylmethoxysilane (CH 2 dCH) 3 SiOCH 3 , tetrakis(dimethylamino)silane Si(N(CH 3 ) 2 ) 4 , and tris(dimethylamino)silane (TDMAS) SiH(N(CH 3 ) 2 ) 3 . TDMAS was determined to be the most effective of these precursors. However, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
125
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(133 citation statements)
references
References 49 publications
8
125
0
Order By: Relevance
“…A reaction involving the breaking of the Si-H bond in the precursor is very unlikely. 24 We propose therefore similar surface chemical reactions during the first ALD half cycle as reported by Burton et al 19 for the SiH(N(CH 3 ) 2 ) 3 precursor which is comparable to the present precursor:…”
Section: Surface Chemistrysupporting
confidence: 90%
See 1 more Smart Citation
“…A reaction involving the breaking of the Si-H bond in the precursor is very unlikely. 24 We propose therefore similar surface chemical reactions during the first ALD half cycle as reported by Burton et al 19 for the SiH(N(CH 3 ) 2 ) 3 precursor which is comparable to the present precursor:…”
Section: Surface Chemistrysupporting
confidence: 90%
“…20 In this respect, the use of precursors with amino ligands has also shown promising results, in particular when combined with H 2 O 2 , O 3 , or O 2 plasma as the oxidant. [21][22][23][24] Very recently, also SiH 4 has been used as Si precursor during plasma-assisted ALD with CO 2 plasma as oxidant. 25 SiO 2 films grown with ALD have been reported to exhibit low carbon content, and a high electrical breakdown field.…”
mentioning
confidence: 99%
“…In ALD processes the precursor structure plays a large role in the deposition process and film performance. A wide variety of molecular structures have been assessed ranging from chlorosilanes 4,5 and alkoxysilanes 6 to aminosilanes 7,8 and alkylaminosilanes 9 . Aminosilanes provide breadth of structural variations and may be more desirable than chlorosilanes from safety and operability perspectives.…”
mentioning
confidence: 99%
“…In order to verify this conclusion an FTIR spectrum of a SiO 2 film coated on silicon was recorded (not shown here). Typical Si-O-Si and Si-OH bonds could be identified, but no organic residuals -indicating a complete oxidation reaction of the precursor material [20,21]. In the FTIR spectrum a broad peak around 3387 cm -1 corresponding to a water absorption band [22] revealed that there is physically absorbed water within the films or pores of the films, respectively.…”
Section: Development Of Ald-coatings For Optical Applicationsmentioning
confidence: 94%